2022
DOI: 10.1016/j.clnesp.2021.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed and fresh food consumption and symptoms of anxiety and depression during the COVID – 19 pandemic: COVID Inconfidentes

Abstract: Background & Aim Psychological disorders are an important health problem worldwide. A healthy diet is recommended as one of the measures to prevent and control mental disorders. Epidemiological studies have shown important associations between the consumption of diets rich in nutrients and a lower risk of developing anxiety and depression. Therefore, the aim of this study was to evaluate the association between the prevalence of anxiety and depression symptoms and food consumption, according to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 75 publications
0
39
0
3
Order By: Relevance
“…Eligible studies included different age groups, including adults (N = 11), adolescents (N = 4), children (N = 1), and mixed-age groups (adolescents and adults (N = 1)). The mean age of all participants was 35.2 years (not including four studies that reported age categories [18][19][20][21]), with a mean age of 44.9 years for adults, 14.5 years for adolescents and 9.6 years for children. In the 16 studies that reported sex proportions, males accounted for 44.5% of the samples combined.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eligible studies included different age groups, including adults (N = 11), adolescents (N = 4), children (N = 1), and mixed-age groups (adolescents and adults (N = 1)). The mean age of all participants was 35.2 years (not including four studies that reported age categories [18][19][20][21]), with a mean age of 44.9 years for adults, 14.5 years for adolescents and 9.6 years for children. In the 16 studies that reported sex proportions, males accounted for 44.5% of the samples combined.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eleven studies modelled ultra-processed food consumption as the exposure variable and mental disorder parameters as the outcome [17][18][19]21,[23][24][25][26]30,48,50], with the remaining six modelling associations in the opposite direction [20,22,[27][28][29]31].…”
Section: Details Of Exposure Variables and Average Ultra-processed Fo...mentioning
confidence: 99%
See 3 more Smart Citations